Anthropogenic activities influence the abandonment of Bearded Vulture (Gypaetus barbatus) territories in southern Africa. (28th January 2015) - Krüger, Sonja C.; Simmons, Robert E.; Amar, Arjun
Abstract: Developing an effective conservation strategy for a critically endangered species relies on identifying the most pressing threats to the species. One approach to elucidate these threats for a long-lived animal with high territorial fidelity is to identify factors associated with territorial abandonment. The Bearded Vulture ( Gypaetus barbatus ) has declined dramatically in southern Africa over the past few decades, with nearly 50% of known territories being abandoned. In this study we examine the evidence for 3 hypotheses: that territorial abandonment was associated with (1) human impact, (2) food availability, or (3) climate change, or a combination of these. Model selection was used to determine the relative importance of 7 covariates within the home range of an adult pair, an area of 10 km radius (314 km 2 ) around each nest. Our analyses provided strongest support for the human impact hypothesis, with abandonment more likely in territories with more power lines and higher densities of human settlements. Additionally, within Lesotho, southern Africa, there was some support for the food shortage hypothesis, with territories more likely to have remained occupied where they had a greater number of feeding sites within close proximity. Our data provided no support for the hypothesis that climate change may be driving abandonment through a direct impact of elevation or nest site aspect. Our results are in accordance with the main causes of mortality: poisoning and power line collisions. We suggest that conservation measures should focus on limiting the development of further human settlements and power lines within 10 km of occupied territories, applying mitigation measures to existing power lines and increasing law enforcement and education in areas still occupied by the species.